Incidence of fraud and adulterations in ASEAN food/feed exports: A 20-year analysis of RASFF’s notifications - Iyiola Oluwakemi Owolabi (Public Library of Science (PLoS), 2021)
This paper explored the occurrence of food fraud and adulterations (FFA) in exports from the Association of South- East Asia Nations (ASEAN), with implications on food chain and international trade. Data from European Union Rapid Alert System for Food and Feed (EU RASFF) about FFA notifications on ASEAN exports for a period of 20 years (2000–2020) were extracted and analyzed. Results from this study revealed that of all ten ASEAN member countries, seven had cases of FFA notified in the database with Thailand (n = 47, 32%) and the Philippines (n = 37, 26%) receiving the highest frequency of notifications in the region. There was a statistical significance difference in frequency of notifications received on products from these seven countries with herbs and spices ranking highest (n = 22, 15%). Highest notifications of FFA on ASEAN exports came from the United Kingdom (n = 31, 21%). All the seven countries experienced border rejections and consequent destruction of food products especially on exports from Indonesia where 95% of product with FFA were border rejected. Border rejections on products from these countries were significantly different. Therefore, a thorough implementation system, appropriate testing and constantly updating each country’s FFA database could aid actions in curtailing future events.